Nitrogen balance, microbial protein synthesis and blood metabolites in fattening of male Bali cattle fed ration with different protein levels in smallholder farms - Tahuk, P. K.; Budhi, S. P. S.; Panjono, P.; Baliarti, E. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
Research was aimed to determine nitrogen balance, microbial protein synthesis, and blood metabolites of male Bali cattle fattening fed ration with different protein level in smallholder farms North Central Timor, Province of East Timor Tenggara, Indonesia. The cattle used were 18 heads aged 2 to 2.5 years with initial body weight of 229.86±12.46 kg. The cattle were randomly divided into three treatment groups. The T0 group was given feed the same as traditional fattening cattle practices by farmers,T1 group fed ration containing 12% crude protein (CP) and 72% total digestible nutrients (TDN), andT2 group fedration containing 15% CP and 72%TDN. Cattle were fed individually for 90 days and drinkingwater ad libitum. The data were analyzedby analysis of variance.Results of research indicated the nitrogen balance, and blood urea nitrogen between T1 and T2 were relatively similar, but those were higher (P<0.05) than T0 . In contrast, microbial proteins synthesis, and blood glucose at 0, 4, and 6 hours before and after feeding were relatively similar between the groups. Blood glucose of T2 at 2 hours after intake were higher (P <0.05) than T0, but was not different with T1 . It can be concluded, that the fattening maleBali cattle fed ration containing 12% CP and 72% TDNimprovedthe nitrogen balance and blood metabolites, butit was no positive effect on the microbial proteins and N synthesis.